Neuroanatomical changes in people with high schizotypy: relationship to glutamate levels. Issue 11 (4th December 2017) - Modinos, Gemma; Egerton, Alice; McLaughlin, Anna; McMullen, Katrina; Kumari, Veena; Lythgoe, David J.; Barker, Gareth J.; Aleman, André; Williams, Steve C. R.
Abstract : Background: Cortical glutamatergic dysfunction is thought to be fundamental for psychosis development, and may lead to structural degeneration through excitotoxicity. Glutamate levels have been related to gray matter volume (GMV) alterations in people at ultra-high risk of psychosis, and we previously reported GMV changes in individuals with high schizotypy (HS), which refers to the expression of schizophrenia-like characteristics in healthy people. This study sought to examine whether GMV changes in HS subjects are related to glutamate levels. Methods: We selected 22 healthy subjects with HS and 23 healthy subjects with low schizotypy (LS) based on their rating on a self-report questionnaire for psychotic-like experiences. Glutamate levels were measured in the bilateral anterior cingulate cortex (ACC) using proton magnetic resonance spectroscopy, and GMV was assessed using voxel-based morphometry. Results: Subjects with HS showed GMV decreases in the rolandic operculum/superior temporal gyrus ( p FWE = 0.045). Significant increases in GMV were also detected in HS, in the precuneus ( p FWE = 0.043), thereby replicating our previous finding in a separate cohort, as well as in the ACC ( p FWE = 0.041). While the HS and LS groups did not differ in ACC glutamate levels, in HS subjects ACC glutamate was negatively correlated with ACC GMV ( p FWE = 0.026). Such association was absent in LS. Conclusions: Our study shows that GMV findings in schizotypy are related to glutamate levels, supporting the hypothesis that glutamatergic function may lead to structural changes associated with the expression of psychotic-like experiences.